Diaqua[N,N′-bis(3-carboxyprop-2-enoyl)pyridine-2,6-dicarbohydrazidato(2–)]cadmium(II) N,N-dimethylformamide disolvate - Cao, Quanfu (International Union of Crystallography, 2009)
In the title complex, [Cd(C(15)H(11)N(5)O(8))(H(2)O)(2)]·2C(3)H(7)NO, the Cd(II) ion is located on a twofold rotation axis and is seven-coordinated in a distorted pentagonal-bipyramidal manner. The asymmetric unit comprises one metal ion, one doubly deprotonated N,N′-bis(3-carboxyprop-2-enoyl)pyridine-2,6-dicarbohydrazide ligand, two coordinating water molecules and two dimethylformamide solvent molecules. In the crystal, a two-dimensional network is formed through N—H⋯O and O—H⋯O hydrogen bonds.